Regioisomeric acylated polyhydroxy triterpenoids from the stems of Barringtonia racemosa. (September 2015) - Annam, Suresh Chandra Venkata Appa Rao; Madhu, Ankireddy; Mangala Gowri, Ponnapalli; Raju, Tuniki Venugopal; Pardhasaradhi, Bobbili Veera Venkata
Graphical abstract: Isolation and structure elucidation of regioisomers of acylated triterpenoids from Barringtonia racemosa is described. Highlights: Isolation of isomers of polyhydroxy acylated triterpenoids from Barrintonia racemosa stem. Their structures were characterized by the interpretation of spectroscopic data. Racemosol B showed moderate but cell-type selective activity. Abstract: From the stem of Barringtonia racemosa two new regioisomeric oleanane-type triterpenes were isolated and characterized as racemosol B (1 ) and isoracemosol B (2 ). The structures were elucidated by the use of spectroscopic methods. In addition, the known compounds lupeol, betulinic acid and bartogenic acid were identified. Racemosol B was evaluated for cytotoxicity against a panel of human tumor cell lines, A-549, MDA-MB-231, HeLa, and K-562 and showed moderate but cell-type selective activity.